A novel class of oxazepine-based anti-cancer agents induces cell death in primary human CLL cells and efficiently reduces tumor growth in Eμ-TCL1 mice through the JNK/STAT4/p66Shc axis. (December 2021) - Vanni, Francesca; Lopresti, Ludovica; Zurli, Vanessa; Kabanova, Anna; Cattaneo, Francesca; Sicuranza, Anna; Gozzetti, Alessandro; Gemma, Sandra; Zisterer, Daniela M.; Bocchia, Monica; Campiani, Giuseppe; Baldari, Cosima T.; et al.
Abstract: Survival and expansion of malignant B cells in chronic lymphocytic leukemia (CLL) are highly dependent both on intrinsic defects in the apoptotic machinery and on the interactions with cells and soluble factors in the lymphoid microenvironment. The adaptor protein p66Shc is a negative regulator of antigen receptor signaling, chemotaxis and apoptosis whose loss in CLL B cells contributes to their extended survival and poor prognosis. Hence, the identification of compounds that restore p66Shc expression and function in malignant B cells may pave the way to a new therapeutic approach for CLL. Here we show that a novel oxazepine-based compound (OBC-1) restores p66Shc expression in primary human CLL cells by promoting JNK-dependent STAT4 activation without affecting normal B cells. Moreover, we demonstrate that the potent pro-apoptotic activity of OBC-1 in human leukemic cells directly correlates with p66Shc expression levels and is abrogated when p66Shc is genetically deleted. Preclinical testing of OBC-1 and the novel analogue OBC-2 in Eμ-TCL1 tumor-bearing mice resulted in a significantly longer overall survival and a reduction of the tumor burden in the spleen and peritoneum. Interestingly, OBCs promote leukemic cell mobilization from the spleen to the blood, which correlates with upregulation of sphingosine-1-phosphate receptor expression. In summary, our work identifies OBCs as a promising class of compounds that, by boosting p66Shc expression through the activation of the JNK/STAT4 pathway, display dual therapeutic effects for CLL intervention, namely the ability to mobilize cells from secondary lymphoid organs and a potent pro-apoptotic activity against circulating leukemic cells. Graphical Abstract: ga1 Highlights: Oxazepine-based compounds promote p66Shc expression selectively in CLL cells through the JNK-dependent activation of STAT4. Oxazepine-based compounds display powerful antitumor effects in the Eμ-TCL1 CLL mouse model. Oxazepine-based compounds restore S1PR1 expression and mobilize CLL cells from secondary lymphoid organ.